La diversidad dentro de la unidad: los aspectos culturales de la fraseología hispana - Szyndler, Agnieszka (Neophilologica, 2012)
This paper aims to analyze the selected phraseological units including names of animals from both syntactic and semantic point of view. The main purpose of our research, carried out in the area of cultural linguistics, is to present lexical differences and similarities not only between Polish and Spanish languages but also between regional varieties of Spanish. We intend to demonstrate that the same phraseological units with zoosemic term may exist only in certain varieties or may be used in distinctly different ways in respective Spanish speaking countries. In other words, it may present differences both in the metaphorical realization (figurative meaning) and image component which forms its conceptual structure.